2014
DOI: 10.1177/1045389x14549872
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the McKibben muscle: Energetics, operating fluid, and bladder material

Abstract: In spite of extensive modeling and characterization efforts, little is known about the energetics of McKibben muscle actuators. This article experimentally investigates the effectiveness of traditional McKibben muscles at converting fluid energy delivered to the actuator to mechanical output work over full actuation cycles. Once these efficiency metrics are established, a comparison of the efficiencies of traditional pneumatic fluidic artificial muscles and hydraulic fluidic artificial muscles is presented. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 25 publications
2
113
0
Order By: Relevance
“…Such an assumption is generally verified in the case of pneumatic artificial muscles working in a typical [1bar-5bars]-range if a sufficiently thin inner tube made of a soft rubber was chosen. Meller et al [21] have recently demonstrated the effects of bladder stiffness on HAM performance with increasingly stiff bladders significantly limiting the maximum strain achieved and slightly reducing the blocked force. A semi-empirical approach was introduced to account for bladder stiffness in the ideal model by introducing fitting parameters  F and   for force and strain, respectively [21]:…”
Section: Effect Of the Inner Tube Stiffness On Ham Performancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an assumption is generally verified in the case of pneumatic artificial muscles working in a typical [1bar-5bars]-range if a sufficiently thin inner tube made of a soft rubber was chosen. Meller et al [21] have recently demonstrated the effects of bladder stiffness on HAM performance with increasingly stiff bladders significantly limiting the maximum strain achieved and slightly reducing the blocked force. A semi-empirical approach was introduced to account for bladder stiffness in the ideal model by introducing fitting parameters  F and   for force and strain, respectively [21]:…”
Section: Effect Of the Inner Tube Stiffness On Ham Performancesmentioning
confidence: 99%
“…As noted by Tiwari et al [20] and Meller et al [21], the use of bulky compressors can be avoided in hydraulic artificial muscles (HAMs), thus making compact design possible. Meller et al [21] have also clearly demonstrated that the HAMs have approximately doubled the energy conversion efficiency of PAMs.…”
Section: Joseph L Mckibben Was the First To Introduce Mckibben Artifmentioning
confidence: 99%
See 1 more Smart Citation
“…To consider the impact of bladder stiffness on the muscle performance, theoretical (Sangian et al, 2015) and semi-empirical (Meller et al, 2014) modifications have been added to the model.…”
Section: Modelling Of Temperature Driven Mckibben Artificial Musclementioning
confidence: 99%
“…The muscle usually operates with pressurized gas/water, and the system requires a compressor/pump as well as a gas/water storage container (Meller et al, 2014;Tiwari et al, 2012;Mori et al, 2010;Moon et al, 2006). The pressurized fluids are used to increase the volume of the inner bladder and subsequently deform the braided sleeve that make up the McKibben muscle.…”
Section: Introductionmentioning
confidence: 99%